2017
DOI: 10.18869/nrip.irj.15.2.173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrotherapy on Health of Cerebral Palsy Patients: An Integrative Review

Abstract: Objectives: Hydrotherapy treatment is a type of complementary therapy which is administered in conjunction with other conventional modes of treatment for the treatment and rehabilitations of cerebral palsy patients. Though it has gained increasing popularity in many countries around the world, its application in Iran is still rare. The aim of this study was to perform an integrative review of the extant literature in the field of hydrotherapy and its applications for the improvement of ICF (International Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…Para a realização da intervenção, foi executado um protocolo com três fases: FI (fase inicial), FIT (fase intermedária) e FF (fase final). Esse protocolo e as suas fases específicas foram construídas a partir de técnicas descritas nos métodos Bad Ragaz (STAN, 2017), Halliwck (SHAMS-ELDEN, 2017) e fisioterapia aquática convencional (KHALAJI et al, 2017).…”
Section: Materiais E Metódosunclassified
“…Para a realização da intervenção, foi executado um protocolo com três fases: FI (fase inicial), FIT (fase intermedária) e FF (fase final). Esse protocolo e as suas fases específicas foram construídas a partir de técnicas descritas nos métodos Bad Ragaz (STAN, 2017), Halliwck (SHAMS-ELDEN, 2017) e fisioterapia aquática convencional (KHALAJI et al, 2017).…”
Section: Materiais E Metódosunclassified
“…6 Iranian researchers Khalaji et al published a comprehensive review of 33 research papers published from 2000 to 2016 on the results of hydrotherapy on patients with CP and concluded that this therapy, when applied in conjunction with other conventional therapies, has positive effects in all areas of the International classification of functioning, disability and health. 7 The Halliwick concept improved motor function in children with CP and autism in swimming and gross motor skills depending on the individual condition of the patient. 8 Meyer et al concluded that for children with cerebral palsy, Halliwick therapy provided significant results in a global reduction in spasticity.…”
Section: Introductionmentioning
confidence: 99%
“…erebral palsy is a non-progressive disease and one of the most common movement disorders in children that leads to shortness, deformities, and functional limitations [1,2]. The damage to the child's brain affects the motor system and leads to reduced coordination, poor balance, and abnormal movement pattern.…”
Section: Introductionmentioning
confidence: 99%